2020
DOI: 10.1080/17512433.2020.1805315
|View full text |Cite
|
Sign up to set email alerts
|

Medication therapy strategies for the coronavirus disease 2019 (COVID-19): recent progress and challenges

Abstract: Introduction: The coronavirus disease 2019 (COVID-19) pandemic has spread globally since it outbroke in December 2019. The urgent pandemic presents an unprecedented challenge to develop and identify effective medication therapy strategies to combat the COVID-19. Areas covered: Here, we summarized and evaluated the current treatment drugs and regimens, and put forward the treatment recommendations, including using the potential repurposed or experimental drugs against COVID-19, e.g. chloroquine (CQ), hydroxychl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“… 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 We excluded 19 CPGs (eFigure in Supplement 1 ). 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 Of the 32 included CPGs, 3 (9.4%) 15 , 38 , 40 reported on pharmacologic treatments for critically ill patients specifically, and the remainder reported on treatments for hospitalized patients with COVID-19. Fifteen CPGs (46.9%) were international 15 , 16 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 We excluded 19 CPGs (eFigure in Supplement 1 ). 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 Of the 32 included CPGs, 3 (9.4%) 15 , 38 , 40 reported on pharmacologic treatments for critically ill patients specifically, and the remainder reported on treatments for hospitalized patients with COVID-19. Fifteen CPGs (46.9%) were international 15 , 16 , …”
Section: Resultsmentioning
confidence: 99%
“…We excluded 19 CPGs (eFigure in Supplement 1). [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] Of the 32 included CPGs, 3 (9.4%) 15,38,40 reported on pharmacologic treatments for critically ill patients specifically, and the remainder reported on treatments for hospitalized patients with COVID-19. Fifteen CPGs (46.9%) were international 15,16,20,21,23,24,27,[31][32][33][34]36,38,43,44 and 17 (53.1%) were national.…”
Section: Cpg Identification and Quality Assessmentmentioning
confidence: 99%
“…However, another observation was that after their COVID-19 infection most patients developed hypoxia, a condition where an individual has an alarming low oxygen saturation level of about 50–80% saturation [ 41 ]. In contrast, the expected saturation level is ≥95% with the patients not experiencing any difficulties in breathing [ 42 , 43 ]. This phenomenon resulted in patients becoming severely ill, especially when accompanied by a lack of dyspnea and extremely low oxygen saturation levels.…”
Section: Discussionmentioning
confidence: 99%
“…There are certain emerging therapies to cope with the infections. Hydroxychloroquine, Chloroquine, Lopinavir/ritonavir and Remdesivir have antiviral activity that can control SARS-CoV-2 in-vitro [32]; moreover, Viral entry inhibitors, ACE2 modulators (angiotensin receptor blockers) and TMPRSS2 inhibitors (camostat mesylate) are promising clinical drugs, and it has suggested that Shuanghuanglian oral liquid and Lianhuaqingwen are effective for certain patients with COVID-19 in China [18,33,34]. Given the high level of cytokines in the host, the immunosuppressive drugs targeting the interleukin-6 (IL-6) receptor, tocilizumab are reported to treat COVID-19-related cytokine storms [35], and the application of blood puri cation technology (plasma exchange, blood/plasma ltration, adsorption, perfusion and continuous renal replacement therapy) is helpful to the removal of cytokines and may be bene cial to improve the clinical outcome of critically ill patients [20].…”
Section: Discussionmentioning
confidence: 99%